Doorway of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The jamb of the doorway is carved with sculptures of Ganga and Yamuna, along with a Shaiva dvarapala (door guardian). The lintel of the sanctum doorway features a two-armed depiction of Lakulisa seated in padmasana (lotus pedestal pose) in dhyana mudra (meditative hand gesture), carrying a lakuta (club) in his left hand and fruit in his right hand, inside a niche on the lalatabimba (lintel). Flanking Lakulisa, there are depictions of a four-armed Brahma and Vishnu on the right and the left hand of the lintel, respectively.